Ramzi, Abd al-Qadir. “The Notion of Creativity in the Islamic System,” Year 11, Issue 41 (Summer 1426 AH/ 2005 CE), Pp. 11-46. - رمزي, عبد القادر هاشم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2005)
Abd al-Qadir Ramzi’s study is an analytical attempt to crystallize the notion of “Islamic creativity” in a systemized context, clarify the conceptual constants in the Islamic system, reveal the relationship between the Islamic system and the Islamic creative mind, and denote the requirements for stimulating Islamic creativity. These are discussed within the following points: creativity in previous Islamic studies; the concept of creativity and its indications in the Qur’an and Sunnah, and in language resources; the paths of creative work; and the organizational groundwork needed to stimulate the concept of creativity in Islamic reality and the requirements of the civilizational reality.